Свод данных об исследованиях курганов на территории Донецкой области в ХХ веке - Усачук, А.Н.; Полидович, Ю.Б.; Цимиданов, В.В.; Литвиненко, Р.А. (Археологический альманах, 2004)
This paper is the summary of data obtained for the barrows investigated in the Donetsk region during the 20th century. The information, among others, includes location, the number of excavated barrows in the groups, families of the excavators’ leaders and main literature sources.